On the art of aggregating "apples & oranges" - Jochen Jesinghaus (Fondazione Eni Enrico Mattei (FEEM), 2000)
The Communication on Environmental Indicators and Green National Accounting (Com (94) 670 final, 21.12.94) laid the basis for indicator and accounting projects aimed to give comprehensive support to environmental policy, like GARP and GreenStamp. The article is intended to demonstrate: that indicators are a powerful driving force of many, if not most, political decisions; that bad indicators are thus a recipe for bad politics; how an indicator system that serves democratic decision-making should be designed. In particular, in order to avoid serious policy distortions, environmental policy needs a broad spectrum of indicators covering all relevant issues. Valuation projects that treat pollutants with sophisticated methodologies like Impact Pathway Analysis (GARP) or Avoidance Cost-based economic modelling (GreenStamp) face data availability problems which force them in practice to concentrate on selected pollutants, excluding all others; the result is policy distortion. The author proposes that valuation methodologies should focus on general patterns, like the dependence of Avoidance Costs from implementation speed, type of instruments, and level of analysis (i.e. company, sector, national economy, EU economy), instead of treating single pollutants with unnecessary precision while neglecting many others. Policy Performance Indices (PPI) may serve as an instrument to extend such general valuations to a broad range of pollutants and policy questions, using numéraires plus relative weighting as the basis for valuations.
Keywords: Q2; Q3; O47; 330; Sustainable development; indicators; indices; environmental valuation; climate change; avoidance cost approach; willingness-to-pay; WTP; Nachhaltige Entwicklung; Wirtschaftsindikator; Willingness to pay; Umweltpolitik; EU-Staaten